Effect of Return on Assets (Roa), Debt Ratio, and Quick Ratio to Value Healthcare Sector Companies on The Indonesian Stock Exchange 2018-2022 - Asnan, Sufi Luthfia; Albertus, Redy Herinanto; Murdo, Ilham Tri (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2024)
This study aims to analyze and test the effect of Return on Assets, Debt Ratio and Quick Ratio on company value in the Healthcare sector listed on the Indonesia Stock Exchange in 2018 - 2022. The method used in this research is quantitative method. The data collected using the Purposive Sample technique were 16 companies with a total population of 33 companies. The data source used in this study is secondary data, namely financial report data published on the official IDX website (www.idx.co.id). The analysis method used is multiple linear regression tests. The results of this study state that Return on Assets has a positive and significant effect on firm value (PBV), Debt Ratio has a negative effect on firm value (PBV), Quick Ratio has a significant positive effect on firm value (PBV), while Return on Assets, Debt Ratio and Quick Ratio simultaneously have a positive and significant effect on firm value (PBV)